Inter-Kingdom Signaling of Stress Hormones: Sensing, Transport and Modulation of Bacterial Physiology - Boukerb, Amine Mohamed; Cambronel, Melyssa; Rodrigues, Sophie; Mesguida, Ouiza; Knowlton, Rikki; Feuilloley, Marc G. J.; Zommiti, Mohamed; Connil, Nathalie (Frontiers in Microbiology, 2021)
Prokaryotes and eukaryotes have coexisted for millions of years. The hormonal communication between microorganisms and their hosts, dubbed inter-kingdom signaling, is a recent field of research. Eukaryotic signals such as hormones, neurotransmitters or immune system molecules have been shown to modulate bacterial physiology. Among them, catecholamines hormones epinephrine/norepinephrine, released during stress and physical effort, or used therapeutically as inotrope have been described to affect bacterial behaviors (i.e. motility, biofilm formation, virulence) of various Gram-negative bacteria (Escherichia coli, Salmonella enterica serovar Typhimurium, Pseudomonas aeruginosa, Vibrio sp.). More recently, these molecules were also shown to influence the physiology of some Gram-positive bacteria like Enterococcus faecalis. In E. coli and S. enterica, the stress-associated mammalian hormones epinephrine and norepinephrine trigger a signaling cascade by interacting with the QseC histidine sensor kinase protein. No catecholamines sensors have been well described yet in other bacteria. This review will aim to report the state of the art of catecholamine’s sensors in eukaryotes and prokaryotes, their transport, and known effects on bacteria.